2004
DOI: 10.1111/j.1468-5584.2004.00254.x
|View full text |Cite
|
Sign up to set email alerts
|

Development of social cognition in infant chimpanzees (Pan troglodytes): Face recognition, smiling, gaze, and the lack of triadic interactions1

Abstract: In this paper, we summarize a series of studies on the developmental changes in social cognition in mother-raised infant chimpanzees from birth to around 2 years old. The infants preferentially tracked a photograph of their mother's face at 1 month but showed indifferent preferences to faces at 2 months old. This change in facial recognition was correlated with a decrease in neonatal spontaneous smiling, increase in social smiling and a decline in neonatal imitation of facial expressions. Also at around 2 mont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
93
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(96 citation statements)
references
References 34 publications
(46 reference statements)
2
93
1
Order By: Relevance
“…Similarly, apes may not show basic co-orienting responses when others move the direction of their gaze, nor more complex forms of reasoning about others' line of sight (e.g. accounting for barriers and distractors) until they are several years old [24,[32][33][34][35][36]. Overall, this evidence supports the proposal that gaze following in non-human primates requires more extensive experience with relevant social interactions than is necessary for humans (e.g.…”
Section: Introductionsupporting
confidence: 72%
See 1 more Smart Citation
“…Similarly, apes may not show basic co-orienting responses when others move the direction of their gaze, nor more complex forms of reasoning about others' line of sight (e.g. accounting for barriers and distractors) until they are several years old [24,[32][33][34][35][36]. Overall, this evidence supports the proposal that gaze following in non-human primates requires more extensive experience with relevant social interactions than is necessary for humans (e.g.…”
Section: Introductionsupporting
confidence: 72%
“…We adopted this approach because rhesus monkeys spontaneously follow the gaze of both conspecifics [42,43] and humans [35]. The actor rotated her entire head upward (with her eyes open), because previous work indicated that macaques show robust gaze-following responses to such cues [35,36], and primates generally are less sensitive to eye cues alone [21,54]. Although it remains possible that monkeys of different ages had different levels of experience with humans and thus responded differentially to the human actor, we note that as a whole this population is highly habituated to human observers from infancy.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, infant chimpanzees and an infant gibbon recognize and prefer the face of their mother or human caregiver over less familiar faces at 1 month of age (Myowa-Yamakoshi and Tomonaga, 2001a;Tomonaga et al, 2004), much like human infants (Pascalis, Deschonen, Morton, Deruelle, and Fabregrenet, 1995). Taken together, these results show that humans and apes exhibit similar developmental trajectories in early infancy, suggesting that human patterns have deep biological roots.…”
Section: Comparative Developmental Psychologysupporting
confidence: 53%
“…Encouraged by these results we performed a preferential looking experiment, an experimental paradigm first used to investigate infant's vision (Fantz, 1963) but recently also used in animal experiments (Shirai et al, 2010;Tomonaga et al, 2004;Shirai & Imura, 2014). This experiment was conducted in a "cat-café" in Fukuoka-city.…”
Section: Experimental Datamentioning
confidence: 99%